Implementasi jaringan internet guna meningkatakan pelayanan pemerintah desa di Kecamatan Sembalun - Muhamad Sadali; Yupi Kuspandi Putra; Yahya Yahya; Intan Komala Dewi (Universitas Hamzanwadi, 2021)
Internet network has become a basic need for all government offices, from central to village governments. This is because the Indonesian government has built an integrated online system. Therefore, this service aims to assist all village governments in Sembalun District in improving services for the community in information technology. The target of the activity is Sembalun District which is the leading partner. The target and outcome of this service are establishing an internet network facility of a village government in Sembalun District to improve services in information and communication technology. The method used is a participatory approach to community development or Participatory Rural Appraisal (PRA). The results of this service are: 1) The internet network facility greatly helps the village government, 2) Village officials can complete their work based online, 3) The village government can improve services in information and communication technology. With the community service that has been carried out, it is hoped that it can help all village governments in Sembalun District carry out their duties to the maximum and improve services for the community.